Decision Support Systems Adoption Among Strategic Decision Makers in Higher Learning Institution in Yemen - Alhamassy, Saleh Ahmad Ali (2012)
It is claimed that higher education institutions in Yemen do not have clear visions, missions, strategic objectives, and they apply traditional management systems with complex procedures. In addition, there has been some ignorance of technology among the Yemeni strategic decision makers because they have not had a clear view of what Information Technology applications can contribute in developing their institutions and the strategic decision-making, and styles of the strategic decision makers. IT applications can also be used in investigating the perceived acceptance of the strategic decision makers towards decision support systems (DSS) technologies. Thus, the unified theory of acceptance and use of technology (UTAUT) has been adopted. A total of 121 forms of questionnaire were collected from the strategic decision makers in Sana’a University and Science and Technology University. Descriptive, regression and structural equation modeling analyses were run to test the hypotheses. The present study found that the research policy, adoption of information technology applications, curriculum, mission, organization of colleges and university, admission policies, financial policies, facilities and equipment, and institutional governance personnel are areas that require strategic decisions in the Yemeni higher learning institutions. Regarding decision making styles, the majority are technical-oriented (analytical and directive) strategic decision makers. The findings indicate that performance expectancy and strategic value expectancy have a significant positive influence on behavioural intention of the strategic decision makers to adopt the DSS. However social influence was found to have influence on behavioural intention when it was tested alone as an independent construct. The strategic decision maker’s decision making style moderates the relationship between efforts expectancy and behavioural intention only. However, administrative experience and professional achievement moderate the relationship between performance expectancy and strategic value expectancy, and behavioural intention only. As a conclusion, this study suggests that technology adoption can be a new strategic decision area.